Factors Affecting the Level of Achieving Employability 4.0 of Hearing-Impaired Special Education Students - Saad, Saffuan; Musta'amal @ Jamal, Aede Hatib; Saud, Sukri; Osman, Sharifah; Hamzah, Fathullah (Journal of Technical Education and Training, 2023)
The use of IR4.0 digital technology, computers and smartphones are gradually changing the scope of employment. This requires special education students with impaired hearing who are enrolled in the Special Skills Certificate programme at Malaysian polytechnics to acquire and master digital skills that will meet the employer’s needs. Therefore, this study is conducted to identify the factors that affect the level of achieving employability 4.0 of impaired hearing special education students in Malaysian polytechnics, from the perspectives of lecturers and employers. Quantitative methods are used in carrying out the study, and the data are analysed using the SPSS V26. The research instrument in the form of a questionnaire is distributed to the respondents and the contents are verified by two experts. This study involves a total of 71 Special Skills Certificate lecturers and 84 employers who have offered industrial training to the special education students with impaired hearing, who use computers and smartphones in their workplace. The analysis requirement test was carried out using a normality test and found that the entire data are normally distributed. Here are the results of the descriptive analysis: from the lecturer's perspective, the attitude of impaired hearing special education students towards the use of digital technology score a high average mean value of 4.18; from the employer's perspective, the required digital technology facilities of impaired hearing special education students score a high average value mean 4.36. Meanwhile, the results by inferential analysis using independent t-test showing a significant difference in teaching experience by lecturers. Students can explore the content of the subjects through the use of software and digital technology applications based on their lecturers’ experience in teaching.  Therefore, the factors that affect the level of achieving employability 4.0 should always be in line with IR4.0 technology that meets the needs of employers. The findings could be used another researcher to identify the other factors affecting the level of achieving employability 4.0 of hearing-impaired special education students in Malaysian polytechnic to keep student’s employability 4.0 aligned with the employers wished.